The anthelmintic efficacy of natural plant cysteine proteinases against the rat tapeworm Hymenolepis diminuta in vivo - Mansur F.; Luoga W.; Buttle D.J.; Duce I.R.; Lowe A.; Behnke J.M. (Cambridge University Press, 2024)
Indexed by WOS/ Scopus